Identification of Candidaspecies isolated from oral pediatric and Identification of its sensitivity to some antifungals - Samy, Ream; Aljaza, Diyaa (University of Thi-Qar Journal of Science, 2023)
In newborns, Candida is responsible for the common oral thrush and rash in skin folds and in the diaper area. Before the advent of modern sanitary measures and topical antifungal treatments, infants died from dehydration due to severe oral mucocandidiasis. Oral thrush is more likely to occur in infants and older adults due to reduced immunity. The study aimed to shed light on the relationship between Thrush and Candidia and To molecular identification of Candidia spp. isolated from Thrush. There are 100 samples of Oral swabs collected from pediatric with Thrush at ages ranging from (1day-12 years). All samples cultured on SDA, MSA and MEA. Several tests were used to identify the types of isolated yeasts, including growth on Chromogenic agar medium, as well as biochemical and molecular tests using primers ITS1, ITS4. The Results found that a six species of Candida were isolated on Chromogenic: C. albicans, C. glabrata, C. tropicalis, C. dubliniensis, C. krusei and C. kefyr, Also, showed the number of yeasts that were genetically diagnosed by molecular diagnosis was five species of yeasts as follows 2 isolates C. tropicalis from 22% and one isolate for each of the following types